The Dynamics of Diglossia in Contemporary Arabic: Between Fusha and ‘Amiyah on Instagram - Khumairoh, Siti Aisyatul (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This research aims to explore the changes in modern Arabic diglossia, emphasizing the relationship between Fusha, ’Ammiyah, and digital media. The concept of diglossia, introduced by Charles A. Ferguson, describes a situation where two forms of a language coexist within the same society but serve different social functions. In the Arabic context, these two forms are Modern Standard Arabic (Fusha) and local dialects (’Ammiyah). However, advancements in digital media have created new communication spaces that blur the functional boundaries between these two linguistic styles. This study employs a descriptive qualitative approach, with data collection methods including observation and documentation of social media content from platforms such as Instagram and other digital outlets. The findings indicate that digital media facilitates code-mixing between Fusha and ’Ammiyah, expands the use of ’Ammiyah into semi-formal contexts, and simplifies the structure of Fusha to make it more accessible and adaptive. These results suggest a shift from traditional diglossic patterns toward more dynamic forms. Consequently, diglossia in modern Arabic is no longer rigid; instead, it undergoes a negotiation of roles in line with the progress of communication technology.